The Effect of Linear Low-Density Polyethylene and Palm Kernel Shell Ash Mixture on the Physical, Mechanical and Degradation Properties of Paving Blocks - Chasri Nurhayati; Nesi Susilawati; Tri Susanto; Winda Marthalia; Aditya Krisna Nugroho; Ahmad Paisan Pane (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
The aim of this research was to evaluate the physical-mechanical parameters of paving stones obtained on the basis of the mixture of linear low-density polyethylene (LLDPE) and palm kernel shell ash (PKSA) waste. The ratio of LLDPE to PKSA waste (% weight) was varied in five treatments: A0 (100:0), A1 (97.5:2.5), A2 (95:5), A3 (92.5:7.5), A4 (90:10) and A5 (87.5:12.5). The physical appearance, thickness, compressive strength, water absorption, and morphological characteristics of the paving blocks were observed. The blocks were observed at ambient temperature, exposed to sunlight, and placed on the ground surface on day 0 and day 365. The results showed that addition of PKSA waste decreased the compressive strength but increased the water absorption capacity without a significant effect on the thickness of the paving blocks. Observation after 365 days showed insignificant decreases of compressive strength and thickness, whereas the water absorption capacity increased slightly. Small cracks and more voids in the surface, and more brittleness were observed. To summarize, composites of LLDPE and PSKA as filler have physical-mechanical properties that can be used for road pavement blocks.